Criminal Responsibility for Criminal Acts of Misuse of Transportation and Trade of Subsidized Fuel Oil (Study of Decision Number 434/Pid.B/Lh/2022/Pn.Mgl) - Hasiholan Sinaga, Rivaldo Grifier; Suwondo, Denny (Jurnal Hukum Khaira Ummah, 2025)
Natural resources are anything that comes from nature that can be used to meet human needs. Indonesia's agricultural products are used for the welfare and prosperity of the people for the development of national development in Indonesia. However, in reality there are still many people who abuse the transportation and trade of subsidized diesel fuel. The criminal act of misuse of the transportation and trade of subsidized diesel fuel is regulated in the provisions of Article 55 of Law Number 22 of 2001 concerning Oil and Natural Gas, the act of transporting, storing distribution, stockpiling and selling Fuel Oil (BBM). Therefore, this research aims to know criminal responsibility of perpetrators of criminal acts of illegal transportation and trading of subsidized fuel, and then to know to apply criminal sanctions to perpetrators of criminal acts of illegal transportation and trading of subsidized fuel in the judge's decision. The approach method used in this research is a sociological juridical approach. The research specifications used are descriptive analysis, primary and secondary data sources and using qualitative analysis. This writing analyzes the problems analyzed using the theory of responsibility and the theory of legal certainty. Based on the research results, the responsibility of perpetrators of criminal acts of illegal transportation and trading of subsidized fuel is to be held accountable for their actions which violate Indonesian criminal law or can be called criminal acts. Criminal responsibility needs to fulfill at least 3 (three) elements formulated by law and there is a criminal threat for the action. Thus, according to this act, it violates Article 40, 9, Paragraph 5, Part Four, Chapter 3 of Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation which amends Article 55 of Law of the Republic of Indonesia Number 22 of 2001 concerning Oil and Natural Gas jo. Article 55 paragraphs (1) 1 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law and other relevant laws and regulations. The application of criminal sanctions to perpetrators of the crime of illegally transporting and trading in subsidized fuel is an act of intentionally misusing the transport and/or trade in government-subsidized oil, gas and/or liquefied petroleum gas, which is a criminal offence.